Study on the Production of Bonded Magnet NdFeB and Polyvinyl Butyral - Mendrofa, Mareanus; Sinuhaji, Perdinan; Muljadi, Muljadi (Talenta Publisher, 2020)
bonded magnet is composite magnet material made by mixing magnetic powder with non-magnetic binder. The process in manufacturing bonded magnet NdFeB made by mixing powder of neodymium iron boron (NdFeB) commercial type MQP-B with a polyvinyl butyral powder using a glass beaker. The comparisons of variation in composing NdFeB magnets powders with a binder of PVB (% weight) are 98:2, 96:4, 94:6 and 93:7 of 8 grams from total mass of the sample. After mixing the powder, it is molded by using a compression molding method with 8 tons pressure for 20 minutes at curing temperature 1600C. The molded samples are conducted by characterizing the physical properties which include measurement of density, microstructure analysis using SEM-EDX and magnetic properties which include measurement of the magnetic field strength using a Gaussmeter and hysteresis curve using VSM. The result of the study shows that the addition of and binder PVB in bonded magnet NdFeB causes a decrease in the density and magnetic field strength. The best result of density and magnetic field in the manufacture of bonded magnets is obtained by the addition of 2 % binder of 5.66 g/cm3 and strong magnetic field of 1862.4 G. the score of Mr = 72.86 emu/g, Ms = 103 emu/gram, Hc = 8.490 KOe and BHmax = 5.1 MGOe was obtained on the addition of PVB 2 %.